IMPLEMENTING PROBLEM BASED LEARNING TO IMPROVE STUDENTS’ SPEAKING ABILITY AT THE TENTH GRADE OF SMK NEGERI 1 FANAYAMA - Daeli, Sinari (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2022)
Speaking is one of important skills in English. Based on the data obtained in preliminary study, some of the students of tenth grade in SMK Negeri 1 Fanayama could not reach the Minimum Competence Criterion (MCC) of English subject thatis 65, asdetermined at the school. Some of students at SMK Negeri 1 Fanayama got weaknesses in speaking skill. This research aimed at improving the students’ speaking ability by implementing Problem Based Learning model. The subject of this research was 10th Grade students which consisted of 14 persons.The instruments of collecting the data were observation paper and test.This research conducted through classroom action research that consisted of two cycles.The result of observation done to the students and researcher showed that there were some undone activities that influence the success of implementation Problem Based Learning model in cycle I. Therefore, those undone activities were considered and improved in cycle II. Furthermore, the test result in cycle I showed that there were 5 students(36%) who passed and 9 students (64%) who failed. However, the test result in cycle II showed improvement of students’ speaking skill. There were 12 students (86%) who passed, and 2 students (14%) who failed. It can be concluded that students’ speaking skill could be improved by using Problem Based Learning model. Therefore, it is recommended to the English teacher to apply Problem Based Learning model in teaching speaking because this model can make students become active, more confident, and enjoyable.